Autologous fat grafting in keloids and hypertrophic scars: a review - Geoffrey Lee; David J. Hunter-Smith; Warren Matthew Rozen (SAGE Publishing, 2017)
Keloid and hypertrophic scars are unique human dermal fibroproliferative disorders of the injured skin and are associated with pain, itch and can cause functional limitations. A number of genetic, systemic and local factors have been identified in the formation of keloids and hypertrophic scars. Studies have shown that adipose-derived stem cells have angiogenic and antiapoptotic properties which has effects on wound healing, soft-tissue restoration and scar remodelling, and thus may have a role in managing keloid scaring. However, this role is not well described in the literature. A systemic review of available literature was thus undertaken, regarding the use of fat grafting in treatment of keloids and hypertrophic scarring. In total, 858 articles were identified, with ten studies ultimately fulfilling inclusion criteria. There were no studies specifically isolating the keloids and hypertrophic group of patients, and thus quantitative data were completely lacking from the literature. There were, however, individual cases described, and qualitatively encouraging clinical results were reported for the use of fat grafting on keloids and hypertrophic scars. Combined with the current theoretical and immunohistochemical understanding through other laboratory and animal studies, fat grafting may play a role in the treatment of keloids and hypertrophic scaring; however, specific evidence is currently lacking. The role for further research is clear.